Chinese furniture in Malaysian and Chinese ancestral homes: a comparative literature review - Li, JiangLi; Anwar, Rusmadiah; P. Toyong, Natrina Mariane (Faculty of Art and Design, 2025)
This systematic literature review addresses critical gaps in transnational material culture research by examining the evolution of Chinese furniture in Malaysian Huaqiao (overseas Chinese) and Malaysian Chinese ancestral homes (1880–1930). Aligned with the Belt and Road Initiatives (BRI’s) cultural exchange objectives, the study employs a PRISMA-guided methodology to synthesize 1,350 sources from CNKI, Scopus, and archival collections. It investigates: (1) mechanisms of aesthetic fusion between Qing Dynasty Cantonese furniture and Malaysian design traditions, (2) sociopolitical and spiritual drivers of diasporic adaptation, and (3) causes of divergent preservation outcomes between Malaysia and China. Thematic coding identifies significant conservation disparities: 68% of Malaysian Chinese ancestral homes implement context-sensitive restoration, contrasting with 82% of Huaqiao homes in China using stylistically inconsistent replicas. Notably, only 9% of the literature engages with BRI-aligned sustainable heritage practices. Key findings reveal furniture served as material manifestations of negotiated cultural identity, merging Cantonese craftsmanship with Malaysian indigenous and British colonial elements. The study contributes a dual-rooted conservation model to bridge preservation gaps and advance transnational heritage governance, underscoring urgent policy interventions for sustaining diasporic cultural identity through material culture. The study contributes a dual-rooted conservation model to advance BRI’s "cultural connectivity" goals.